The Effect of the Team Quiz Learning Model on Thematic Learning Outcomes of Class IV Students in State Elementary School - Hetdy Sitio; Winmery Lasma Habeahan (research, training and philanthropy institution Natural Aceh, 2023)
This study was to determine the effect of the quiz team learning model on the thematic learning outcomes of sub-theme 3 of my parents' work in class IV SD Negeri 091281 Batu IV. This type of research used in this research is a quantitative experimental method with a one-group pretest-posttest research design. In this study, the population was all fourth-grade students at SD Negeri 091281 with a total of 38 people, and the research sample was group A with a total of 24 students. The sampling technique is purposive sampling. Data collection techniques in this study used the results of multiple-choice test questions. The data analysis technique used is the Normality Test and Hypothesis Test. The results of calculations using the paired sample test obtained tcount = 19.096 > ttable = 1.713. From these results, it can be seen that Ho is rejected, which means that using the quiz team learning model affects the thematic learning outcomes of class IV SD Negeri 091281 Batu IV.